2020
DOI: 10.3866/pku.whxb202009063
|View full text |Cite
|
Sign up to set email alerts
|

Selective Exposure of BiOI Oxygen-Rich {110} Facet Induced by BN Nanosheets for Enhanced Photocatalytic Oxidation Performance

Abstract: Photocatalytic oxidation is a promising technology for governing emission of environmental pollutants and managing energy crisis. Typically, the photocatalytic performance of photocatalysts is highly dependent on the type of exposed crystal surfaces. As a semiconductor oxide photocatalyst, the different exposed crystal surfaces of bismuth oxyiodide (BiOI) exhibit different photocatalytic oxidation performances. In this study, we chose BiOI as the model material and provided a novel method to improve the photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…These two low binding energy peaks (189.1 eV and 187.6 eV) are the red-shifted relative to the location of the block boron, which is most likely the existence of two different B-B bonds in the block boron. The peak observed at 191.4 eV is attributed to the complete oxidation state of boron in B 2 O 3 , and the binding energy value is consistent with previous reports [ 16 ]. At the same time, it is observed that the proportion of boron oxide peak is very small, and mainly B-B peak with the binding energy of 187.6 eV related to B-B bonding is the most dominant.…”
Section: Experiments and Discussionsupporting
confidence: 91%
“…These two low binding energy peaks (189.1 eV and 187.6 eV) are the red-shifted relative to the location of the block boron, which is most likely the existence of two different B-B bonds in the block boron. The peak observed at 191.4 eV is attributed to the complete oxidation state of boron in B 2 O 3 , and the binding energy value is consistent with previous reports [ 16 ]. At the same time, it is observed that the proportion of boron oxide peak is very small, and mainly B-B peak with the binding energy of 187.6 eV related to B-B bonding is the most dominant.…”
Section: Experiments and Discussionsupporting
confidence: 91%
“…[47,48] In addition, the peak in O 1s spectra in Figure S3c (Supporting Information) can be divided into two peaks that belong to hydroxyl species (O1, 531.5 eV) and chemisorbed water (O2, 532.6 eV). [49][50][51] It is obvious that the hydroxyl species are the most prevalent kind of oxygen, which supports the in situ introduction of Ni element even more. [52,53] These results confirm that a loading amount of active elements is present in Pd/NF.…”
Section: Resultsmentioning
confidence: 83%
“…First, the photocatalytic activities of BiOCl nanosheets exposed with the (010) and (001) facets were tested to screen a superior surface for the introduction of oxygen vacancies to investigate the surface adsorption and reaction behaviors, and BiOCl (010) was selected due to the higher production yield of CH 3 OH compared to the BiOCl (001) sample (Figure S2). Thus, the following surface adsorption behaviors for both CH 4 and O 2 were studied on the oxygen vacancy-modified BiOCl (010) surface. Interestingly, the optimal adsorption site of CH 4 was determined to be the Bi metal site instead of the oxygen vacancy on BiOCl (010) with or without the oxygen vacancy (Figure ), considering the adsorption energies on different adsorption sites (Figure S2).…”
Section: Resultsmentioning
confidence: 99%